Evaluation of Women's Knowledge about Risk Factors and Early Detection of Breast Cancer at Ibn Rushd College of Education in Baghdad University - alabbody, Huda; alwan, nada; attoof, wafa; ryad, bydaa (Iraqi National Journal of Nursing Specialties, 2017)
Objective: Evaluation of women's knowledge about risk factors and early detection of breast cancer atIbn Rushd college of education in Baghdad University.Methodology: The study sample included (184) women in the Ibn Rushd College / University ofBaghdad, whose age ranged between (17-58) years. Data were collected through a structuredquestionnaire prepared by the National Cancer Research Center which were answered during a scientificsymposium about breast cancer. The score was calculated by correcting the results of the answer, givingone score for each correct answer and then estimating the level of knowledge and inputting all data in astatistical program.Results: The results showed limited level of women's knowledge about risk factors. As good, mediumand weak answer ratios of (11%).(21%) and (69%) each, respectively. . The study revealed no significantrelationship between the level of knowledge with age, occupation and married status (p < 0.05)). therewas more than half of a correct answer to some risk factors such as, increase the probability of diseasewith age (53%), obesity in postmenopausal (53%) or breast self-examine once a month after themenstrual cycle (69 %,), and more than 60% consent increasing physical activity and good nutrition andmaintaining a healthy weight and stay away from abuse hormones, alcohol be able to prevent of breastcancerRecommendations: Promoting public education and awareness campaigns on the risk factors for breastcancer among women in university is mandatory to control the disease